Determination of Dynamic Progressive Collapse Resistances for Deteriorating Multi-story RC Frames Subjected to Column Removal Scenarios via the Energy-based Method - Chen, Jian-Bing; ICASP14; Ding, Luchuan (My University, 2023)
The alternate path method is widely employed to perform progressive collapse analyses of reinforced concrete (RC) structures subjected to sudden column removal scenarios. To avoid cumbersome direct dynamic analyses, the energy-based method (EBM) is an alternative efficient approach to predict the maximum dynamic responses. However, the EBM cannot directly determine dynamic collapse limit states with respect to multi-story RC frames subjected to column removal scenarios, because the deteriorating behavior or the development of cumulative damage in the structural systems. In this contribution, an EBM-intersection point (IP)-based method is proposed to determine the collapse limit states when EBM is adopted to calculate maximum dynamic responses. Considering both an edge column loss case and a middle column loss case with regard to a six-story six-bay RC frame, both deterministic and stochastic analyses are carried out to validate the proposed approach and to calibrate the associated coefficients. According to the results, the proposed method is verified to be effective. Moreover, a Gumbel distribution Gu(0.982,0.009) is adopted to fit the PDF of the coefficient related to the displacements at the collapse limit states, while a lognormal distribution LN(1.031,0.007) is adopted to capture the PDF of the coefficient associated with the resistances.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED